Ethnic cleansing in Western Anatolia, 1912-1923 - Eser, Ümit. (Edinburgh)
x, 297 sayfa
Keywords: ''The Greek landing in Smyrna in May 1919 is widely seen as the catalyst of the Turkish national struggle but even during the chaos of between 1919-1923, the diverse peoples of Asia Minor coexisted and created astonishing but fragile infra-national solutions. In sharp contrast to popular history, this book tells the often-overlooked story of cooperation and resistance in a province renowned for its rich and prosperous ethnic and religious diversity in the face of a larger geopolitical struggle. As such, this research demonstrates that even the most contested national conflicts can display a remarkable degree of capacity for coexistence at the local level, a capacity that is all too easily forgotten amid global conflicts today.'' --